2022
DOI: 10.1186/s12934-021-01728-7
|View full text |Cite
|
Sign up to set email alerts
|

PglB function and glycosylation efficiency is temperature dependent when the pgl locus is integrated in the Escherichia coli chromosome

Abstract: Background Campylobacter is an animal and zoonotic pathogen of global importance, and a pressing need exists for effective vaccines, including those that make use of conserved polysaccharide antigens. To this end, we adapted Protein Glycan Coupling Technology (PGCT) to develop a versatile Escherichia coli strain capable of generating multiple glycoconjugate vaccine candidates against Campylobacter jejuni. Results We generated a glycoengineering E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
2
4
0
Order By: Relevance
“…The absence of significant reactivity of the antibody against 6xHis until the cells are permeabilised may be a consequence of the C-terminal location of the tag and topology of the proteins in the membrane. As demonstrated in previous studies, we observed that glycosylation of NetB was temperature dependent (P < 0.05) [15]. However, a temperature-dependent effect was not observed with FlpA glycosylation.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The absence of significant reactivity of the antibody against 6xHis until the cells are permeabilised may be a consequence of the C-terminal location of the tag and topology of the proteins in the membrane. As demonstrated in previous studies, we observed that glycosylation of NetB was temperature dependent (P < 0.05) [15]. However, a temperature-dependent effect was not observed with FlpA glycosylation.…”
Section: Resultssupporting
confidence: 84%
“…As demonstrated in previous studies, we observed that glycosylation of NetB was temperature dependent (P < 0.05) [ 15 ]. However, a temperature-dependent effect was not observed with FlpA glycosylation.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Expression of heterologous genes from the chromosome rather than multicopy plasmids is a well-recognised strategy for alleviating the toxic effects of metabolically burdensome enzymes, such as PglB, which resides in the cytoplasmic membrane ( Bentley et al 1990 ; Bassalo et al 2016 ; Englaender et al 2017 ). However, in a recent study, Terra et al integrated the entire unmodified pgl pathway onto the chromosome of the chassis strain SDB1 ( wecA - and waaL -; Terra et al 2022 ) and observed greater glycoconjugate yield in 3 out of 4 acceptor proteins tested when an additional inducible copy of pglB was also provided on a plasmid. Optimal glycosylation was achieved when both the glycan biosynthesis genes and pglB were encoded on a plasmid in their native configuration.…”
Section: Discussionmentioning
confidence: 99%